(untitled) (Fiep Bulletin - online, 2014)
The concurrent training (strength and endurance) is associated to mechanisms that could increase performance during exercise, despite involved mechanisms are unclear, there is a hypothesis that the muscle submitted to a conflict situation can’t adapt to both training models. There are controversial points at present literature about it, principally about the kind of strength training, sequence and training volume. Because the variety of designs of studies is very difficult to visualize and compare it, there are a lot of studies and different protocols of training. When we can compare similar trainings in studies, we can see that explosive and concentric strength training increase neural adaptation in muscle and can increase aerobic training performance. Running economy appears like an important factor related to an increase in aerobic training performance; many factors that increase aerobic performance are related to strength training. According papers used in the research, we can say that neural adaptation as result as strength training can increase performance during aerobic training through running economy.